2020
DOI: 10.1038/s41467-020-19818-2
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for increased transmissibility from recurrent mutations in SARS-CoV-2

Abstract: COVID-19 is caused by the coronavirus SARS-CoV-2, which jumped into the human population in late 2019 from a currently uncharacterised animal reservoir. Due to this recent association with humans, SARS-CoV-2 may not yet be fully adapted to its human host. This has led to speculations that SARS-CoV-2 may be evolving towards higher transmissibility. The most plausible mutations under putative natural selection are those which have emerged repeatedly and independently (homoplasies). Here, we formally test whether… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
284
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(317 citation statements)
references
References 69 publications
(97 reference statements)
16
284
4
Order By: Relevance
“…A global analysis of SARS-CoV-2 genomes reported that recurrent mutations did not increase the number of descendants, arguing against positive selection of mutants (22). However, as the present study has revealed, transmissible variants expand in niches that reflect population heterogeneity and avoidance of defensive herd immunity and viral competition.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…A global analysis of SARS-CoV-2 genomes reported that recurrent mutations did not increase the number of descendants, arguing against positive selection of mutants (22). However, as the present study has revealed, transmissible variants expand in niches that reflect population heterogeneity and avoidance of defensive herd immunity and viral competition.…”
Section: Discussionmentioning
confidence: 48%
“…However, as the present study has revealed, transmissible variants expand in niches that reflect population heterogeneity and avoidance of defensive herd immunity and viral competition. Therefore, even if the virus is highly transmissible, it cannot spread freely throughout the world, so a collective analysis of the world's subtypes (22) does not reveal a niche spread. Such context-sensitive propagation of the subtypes could only be visualized by scrutinizing the local spread.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene mutations continue to occur in the process of transmission from person to person because of the error-prone viral FNA polymerase and RNA editing. 27 However, even if mutations continue to occur, they are not selected unless they are new protein changes that further increase the efficiency of virus transmission. As the mutation epidemic curve shows, the emergence of new mutations associated with virus spread have peaked out, strongly suggesting that there is little room for mutations to make more fit viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Second, coinfection of same host due to a recombination between two viral lineages may trigger genomic variability [ 20 ]. Third, mutations acquired through evolution can undergo induction by host RNA editing mechanisms which is associated with innate immune response [ 21 , 22 , 23 ]. Currently, there is no evidence that recurrent mutations in SARS-CoV-2 can lead to increased viral transmission.…”
Section: Sars-cov-2 Mutation Mechanismsmentioning
confidence: 99%